(untitled) (PerCursos, 2022)
This article aims to approach the role of the geotechnologies (orbital remote sensing, geographical information systems and global positioning systems - GPS) and their implications for the geographical knowledge from Milton Santos’ work, and show examples of the role of information technologies and their technical systems for the production and support of territorial public policies. Information technologies understood as technical-informational density of the geographical space, lead to new ways of use, organization and regulation of the territory. The technical systems that involve geotechnologies tend to the technical unicity and to the totality of the places, making possible the instantaneity and simultaneity of the information and then, the qualitative growth of the cognoscibility of the planet. Some limitations of the geotechnologies that could lead to reductionism of understanding of the geographical space to its instrumental forms are shown and the latent possibilities of different uses to the sense in which they were conceived.